The Effectiveness of Education about Healthy Food on Mother's Motivation and Knowledge of Mothers in Preventing the Risk of Stunting - Enok Sureskiarti; Aprin Rusmawati; Gatra Zakky Sabbily; Tiara Adinda Aulia (Universitas STRADA Indonesia, 2025)
Background: Stunting is a health problem caused by chronic malnutrition in children, which affects cognitive and motor growth and development. The role of mothers is very important in preventing stunting, especially through a good understanding of nutritional intake. The issue of stunting in Indonesia is a significant chronic nutritional problem caused by inadequate nutritional intake and various other factors, including maternal Motivation and knowledge about healthy food. Purpose: This study aims to evaluate the effectiveness of nutrition education through animated videos and booklets in improving maternal Motivation and knowledge to prevent the risk of stunting. Methods: This study used a Quasi-Experimental design with a pre-test and post-test with control group design. The sample consisted of 60 mothers who had toddlers at the Kelapa Gading Sehat Posyandu (animation video group) and the Amalia Posyandu (booklet group), each consisting of 30 people. Data were collected using a questionnaire and analyzed using a paired t-test and an independent t-test to see the effectiveness of the educational intervention. Results: he results showed a significant increase in mothers' motivation and Knowledge after being given education. In the animated video group, the average motivation score increased from 35.8 to 48.9, while in the booklet group it increased from 36.4 to 49.8 (p-value = 0.000). The results showed that the average maternal knowledge scores significantly increased after the intervention, with a p-value < 0.05. Conclusion: This study concludes that nutrition education based on animated video media and booklets can be an effective method in increasing mothers' motivation and Knowledge in efforts to prevent stunting.